KESEIMBANGAN KEMAMPUAN DIGITALN DAN KECERDASAAN SPIRITUAL DALAM PENDIDIKAN ISLAM DI ERA SOCIETY 5.0 - Wardatul Jannah; Sufiya; Andi Jaka Ditiya; Abdullah Adib; Rifqi Khairul Anam (Makkah: Journal Of Islamic Studies, 2026)
The Society 5.0 era presents both opportunities and challenges for Islamic education, particularly in maintaining a balance between digital competence and spiritual intelligence. This study aims to analyze the importance of integrating these two aspects in developing Muslim generations who are capable of adapting to technological advancements while preserving Islamic values. This research employs a qualitative approach using a library research method. Data were collected from various scientific sources, including books, national and international journals, and relevant policy documents. The data were analyzed through content analysis to identify concepts, challenges, and strategies for developing digital competence and spiritual intelligence within Islamic education. The findings reveal that digital competence is an essential skill for responding to the demands of Society 5.0; however, it must be balanced with spiritual intelligence as a moral and ethical foundation for the responsible use of technology. The integration of digital literacy, Islamic digital ethics, character education, and strengthened collaboration among families, schools, and communities are key strategies for achieving this balance. Therefore, Islamic education can produce generations who are technologically proficient, morally grounded, and capable of utilizing technology for the benefit of society and humanity.